Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1124/jpet.117.243048
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Calcium/Calmodulin-Dependent Protein Kinase II in Chronic Pain

Abstract: Chronic pain, often defined as any pain lasting more than 3 months, is poorly managed because of its multifaceted and complex mechanisms. Calcium/calmodulin-dependent protein kinase II (CaMKII) is a multifunctional serine/threonine kinase that plays a fundamental role in synaptic plasticity, learning, and memory. Recent emerging evidence demonstrates increased expression and activity of CaMKII in the spinal cord and dorsal root ganglia of various chronic pain models. Moreover, our previous studies also find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 99 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…Currently, the World Health Organization (WHO) analgesic ladder remains the golden standard for the management of CIBP in clinic [3] , [4] . However, current therapeutic strategies often provided inadequate pain relief and are associated with numerous unavoidable side effects which limit their prolonged application [5] , [6] . Despite marked advance has been made regarding the mechanisms of CIBP, few effective drugs has been developed for the management of CIBP in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the World Health Organization (WHO) analgesic ladder remains the golden standard for the management of CIBP in clinic [3] , [4] . However, current therapeutic strategies often provided inadequate pain relief and are associated with numerous unavoidable side effects which limit their prolonged application [5] , [6] . Despite marked advance has been made regarding the mechanisms of CIBP, few effective drugs has been developed for the management of CIBP in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…3537 The activation of CAMKII was proven to participate in cyclic adenosine monophosphate response element-binding protein (CREB) phosphorylation. 38,39 The activated CaMKII/CREB pathway has been extensively confirmed in different pain models. 28,40,41 In an inflammatory pain model, sinomenine was reported to attenuate mechanical allodynia and thermal hyperalgesia by down-regulating the CAMKII/CREB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that increased intracellular calcium concentration ([Ca 2+ ] i ) is a key contributing to neuropathic pain . Thus, we investigated whether ERK gene silence alters [Ca 2+ ] i in DRG neurons by performing calcium imaging.…”
Section: Resultsmentioning
confidence: 99%